Political Space of Society Studies: A Systematic Siterature Review (SLR) - Putri, Virani Nabillah (Internasional Journal of Politics and Public Policy, 2024)
This article aims to review literature regarding community political space, including the concept, forms of participation, factors that influence it, and the challenges faced in Indonesia. The research method used in this research is Systematic Literature Review (SLR) by analyzing 150 scientific articles sourced from the Scopus Database. Article review using the Vosviewer application. The research results show that community political space is characterized as a forum for social participation and political decision making. There are two types of community political participation: traditional ones such as elections and unconventional ones such as protests. The political system, the degree of community political awareness, and civil rights are some of the variables that influence this. It is hoped that the findings of this research will make a significant contribution to the field of aspirational politics research and influence future discussions and investigations. The fact that this research paper only draws from the Scopus database means that its conclusions cannot fully capture political ambitions around the world.